faktor-faktor yang mempengaruhi kejadian retensio plasenta di RSUD polewali mandar tahun 2021 - sitti aras diana (Jurnal Kesehatan Marendeng, 2021)
Abstract. Placental retention is the retention or not delivery of the placenta until or more than 30 minutes after the baby is born. Retention of the placenta can be caused by various factors, namely maternal factors such as parity, maternal age, and uterine factors such as a history of retained placenta and a history of endometritis. This study aims to obtain an overview of the factors that influence the incidence of retained placenta at the Polewali Mandar Regional General Hospital in 2018-2021. This study is a descriptive study, the sample in this study amounted to 100 cases using total sampling technique. Of the 100 mothers with retained placenta, the most occurred at risky ages (<20 years and >35 years) as many as 70 people (70%) and at least at the age of 20 years-35 years as many as 30 people (30%). Of the 100 mothers with retained placenta the most occurred in parity grande multipara as many as 50 people (50%), and the least in parity primiparas as many as 15 people (15%). Of the 100 mothers with retained placenta the most occurred in mothers with moderate anemia as many as 40 people (40%) and the least in mothers with mild anemia as many as 25 people (25%). Of the 100 mothers with retained placenta, the most occurred at the age of <20 years and >35 years, parity grande multipara, and moderate anemia. While the least at the age of 20-35 years, parity primi para, and mild anemia. Therefore, it is expected that the Polewali Mandar Regional General Hospital and staff, especially midwives, can improve the quality of antenatal care services in an effort to reduce the incidence of maternal delivery with retained placenta.